Associations of dietary and sedentary behaviours of pregnant women with their children’s birth weight: findings from the CHAT trial in Australia - Huilan Xu; Limin Buchanan; Yong Wang; Philayrath Phongsavan; Louise A Baur; Li Ming Wen (Public Health Nutrition, 2023)
Abstract